The Impact of War on Ukraine’s Tourism Sector: Global Challenges and Implications - Domyshche-Medyanyk, Alla; Brenzovych, Kateryna; Ronai, Lerri; Domyshche, Aleksandra Alla (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The article examines the development of the tourism industry in the context of the war in Ukraine. It considers global challenges for the tourism business in the context of a security imbalance and analyses the sustainability and adaptability of tourism in Ukraine against the background of the outbreak of hostilities. It also outlines the prospects and directions for the revival and development of the tourism industry in the post-war period. The article aims to study the impact of the war in Ukraine on the formation of global challenges in the field of tourism, to analyse the extent of the damage caused, the problems and peculiarities of the development of the tourism industry in the context of war, and to assess the socio-economic sustainability of the tourism business and the prospects for its post-war recovery. The following research methods were used in writing the article: abstract and logical methods to summarise scientific approaches to the impact of war on the state and development of global tourism, systematisation methods to identify barriers and threats to the tourism business in times of war, and statistical analysis methods to assess tourism development indicators at the global and national levels. To assess the economic and social sustainability of tourism, the author proposes an own approach that combines the index method and the time series method to compare the growth rates of economic and social indicators of the tourism industry with similar indicators of the economy as a whole for a given period. The indicators used were: social indicators of tourism development (number of employees, average salary) and economic indicators (sales of tourism services, capital investments and profitability). The analysis results showed a relatively high economic resilience of tourism in Ukraine over the past six years, despite significant turbulence associated with the COVID-19 pandemic and the war, due to the high mobility and adaptability of the tourism business. Social sustainability is comparatively lower, as this sector uses numerous staff adaptations. A SWOT analysis of the tourism industry in Ukraine during the war was conducted, which allowed us to identify the main barriers and, strategic prospects and directions for the revival of the industry in the post-war period. The comparative analysis method was used to assess the impact of other conflicts on tourism and the possibilities of using the experience of post-war recovery (examples from Syria, Croatia, Israel, and Georgia). It is determined that the development of tourism in the post-war period will depend on ensuring security in the country and attracting investment and opportunities to diversify tourism products by the new conditions.